A new genus and three new species of Drilonematidae (Rhabditida, Drilonematoidea) from earthworms - Ivanova, Elena S.; Hope, W. Duane (Zootaxa, 2009)
A new genus and three new species of Drilonematidae (Rhabditidae, Drilonematoidea) from earthworms deposited in the collection of Natural History Museum, Smithsonian Institution are described and illustrated. Paradicelis bursata gen. et sp. n. is closely related to other Dicelinae genera, namely Dicelis Dujardin, 1845 and Adieronema Timm 1966, but is differentiated from both by the presence of a bursa and by whip-like copulatory sensilla. From Dicelis the new genus differs further by the excretory pore being situated in front of the nerve ring. Dicelis eudrilii sp. n. is the first African member of a predominantly Palearctic genus and also shares similarity with Adieronema, but clearly differs from this genus by the eggs lacking a bipolar corona. D. eudrillii is distinguished from other members of Dicelis by having a narrow, conoid tail; prominent excretory pore; nerve ring being situated around the intestine in both adults and juveniles; very long spicules; and by a well-developed spermatheca. Pharyngonema chinense sp. n. is distinguished from the only other member of the genus, Ph. mekongianum, by the shape of the head end with its minute apical tip; smaller circular lateral organs situated at mid-pharyngeal length; larger, slightly bent spicules with blunt, hooked distal process; and smaller, proximally broadened, club-shaped gubernacula. A specimen of Ph. chinense is described with the distal portion of testis forked. Keys to the genera of subfamily Dicelinae and species of Dicelis, Adieronema, Paradicelis and Pharyngonema are presented.